Cohesion and harmony in the poem "Three Pictures" by poet Mahmoud Darwish - Albzour, Ahmed Mohammad (Arab Journal for Sciences and Research Publishing, 2020)
The research aims to stand on the concept of textual cohesion, and we seek through it to provide a holistic approach to the mechanisms of formal cohesion in the poem, and to explain its role in achieving textual harmony, which is represented by referral, repetition and interconnection, for this research seeks to reveal the elements of cohesion and textual harmony in the poem of three images, has been adopted The research on the descriptive approach, based on that on analysis and statistics, has concluded that the poem is characterized by a coherent and coherent framework, and its parts are linked in an interrelated manner.